Pengaruh Fasilitas dan Disiplin Kerjas terhadap Kinerja Karyawan (Literature Review Manajemen Kinerja) - Sari, Novita; Fauzi, Achmad; Pebiyanti, Elsa; Dayanti, Helmi; Khotimmah, Nurul; Intan Tasia, Sarah; Husniyyah, Tsamara; Sutendi, Zhakila (Dinasti Review Publisher, 2023)
This studyiaims toianalyze theieffect ofiworkifacilities, andiwork disciplineion employeeiperformance. Iniaddition, workidiscipline hasia significantipositive effection employeeiperformance. higher employee discipline is reflected in punctuality. compliance with working hours regulations, high work ethic, and willingness to accept sanctionsifor violations To further improve employee performance. employees must be disciplined forithe sakeiof thei continuitylof thelgoals ofihe organization or company. because they are always subject to the discipline regulated by laws and regulations, and will be implemented as appropriate. The rules of labor standards that are set.